Development of a TaqMan-based dosage analysis PCR assay for the molecular diagnosis of 22q11.2 deletion syndrome - Gunewardene, Siyath; Chandrasekharan, Naduviladath V.; Gnanam, Vaz S.; Ranaweera, Dinali M.; Silva, Deepthi C. de; Samarasinghe, Duminda; Kugalingam, Nirosha; Samarasinghe, Sumudu R.; Madushani, Wadumesthri Y.; Perera, Shehan; Jayaweera, Hiran H. E.; Muneeswaran, Kajan (Genes & Genetic Systems, 2025)
A hemizygous 1.5–3.0-Mb microdeletion of human chromosome 22q11.2 with the loss of multiple genes including histone cell cycle regulator (HIRA) causes 22q11.2 deletion syndrome (22q11.2 DS), a common disorder with variable manifestations including congenital malformations affecting the heart, palate and kidneys in association with neurodevelopmental, psychiatric, endocrine and autoimmune abnormalities. The aim of this study was to develop a TaqMan-based dosage analysis PCR (TaqMan qPCR) for use as a rapid, cost-effective test for clinically suspected patients fulfilling previously described criteria for molecular diagnosis of 22q11.2 DS in a lower middle-income country where the cost of testing limits its use in routine clinical practice. Nineteen patients were recruited with informed consent following ethical approval from the Ethics Review Committee, Lady Ridgeway Hospital for Children, Colombo. Dosage analysis of extracted DNA was performed using a TaqMan qPCR assay by amplifying regions within the target (HIRA) and control (testin LIM domain protein (TES)) genes of suspected patient (P) and unaffected person (N) samples. For detection of a deletion, the normalized value (HIRA/TES dosage) of a P sample was compared with that of an N sample. A ratio of P:N of 0.5 confirmed the presence of a deletion while a ratio of 1.0 refuted this. Seven of the 19 patients were found to have a HIRA deletion, confirming the diagnosis of 22q11.2 DS, with these results being in complete agreement with those of fluorescence in situ hybridization (FISH) (performed in nine of the 19 cases) and whole-exome sequencing (all 19 samples tested). This TaqMan qPCR assay was able to reliably distinguish HIRA-deleted cases from non-deleted ones. The assay was both cheaper and faster compared to commercially available alternatives in our setting, including FISH and multiple ligation-dependent probe amplification.